2006
DOI: 10.1021/bi0524870
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Multidrug Transporter Substrates within Model Membranes

Abstract: Active extrusion of drugs from the cell interior by primary and secondary efflux pumps is an essential mechanism underlying the phenomenon of multidrug resistance. The first discovered and best characterized primary efflux pump found in humans is the ABC transporter P-glycoprotein (PGP), which shows very broad substrate specificity. Many of these molecules are lipophilic, and binding most likely takes place within the membrane. PGP could either translocate them from the inner to the outer leaflet (flippase) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 74 publications
4
56
0
Order By: Relevance
“…4). Maximum peak intensities for all aromatic resonances are found between positions C-3 and G-3 of the lipid chain, in agreement with similar studies of aromatic molecules in lipid membranes (3,9,10).…”
Section: Mas-noesy Measurements On Dopc Membranes Doped Withsupporting
confidence: 90%
See 2 more Smart Citations
“…4). Maximum peak intensities for all aromatic resonances are found between positions C-3 and G-3 of the lipid chain, in agreement with similar studies of aromatic molecules in lipid membranes (3,9,10).…”
Section: Mas-noesy Measurements On Dopc Membranes Doped Withsupporting
confidence: 90%
“…However, it has been demonstrated numerous times that aromatic ring structures do not penetrate into the chain region of lipid membranes (3,9,21). This has been attributed to numerous factors, including the entropic cost associated with intercalating a rigid ring structure into the mobile chain region (3), the fact that asymmetric aromatic molecules have dipole moments that cannot easily be accommodated in the nonpolar chain region of the lipid membrane (25), and the enthalpic requirements of hydroxy, carbonyl, and other substitutions on the ring to fulfill their hydrogen bonding potential (26,27) (which cannot be achieved in the lipid chain region).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most affected were the signals of protons associated with the lipid glycerol backbone and a few upper groups of lipid acyl chains. A similar localization was reported for genistein in DMPC membranes [70]. Additionally, it was shown that the spatial orientation in the bilayer depended on the position of the polar centre of the flavonoid molecule [69].…”
Section: Discussionsupporting
confidence: 80%
“…Cholesterol, in addition to stabilizing membrane structures, may further increase lipid insertion of hydrophobic drugs or xenobiotics. In addition, amphiphilic, positively charged drug compounds, e.g., doxorubicin, mitoxantrone, or verapamil, interact with negatively charged lipid headgroups, while the hydrophobic parts of these drugs interact with apolar membrane regions (Siarheyeva, Lopez, & Glaubitz, 2006;Speelmans, Staffhorst, De Wolf, & De Kruijff, 1995). Therefore, membrane lipids might significantly affect the plasma membrane concentrations and availability of ABCB1 or ABCG2 substrates.…”
Section: P0135mentioning
confidence: 99%